Assessment of energy management and power quality improvement of hydrogen based microgrid system through novel PSO-MWWO technique - Hafiz Ghulam Murtza Qamar; Xiaoqiang Guo; Ehab Seif Ghith; Mehdi Tlija; Abubakar Siddique (Scientific Reports)
Abstract A hybrid microgrid powered by hydrogen is an energy infrastructure that depends on hydrogen as its primary energy carrier within a localized network. This study proposed a novel bi-level optimization approach to enhance power quality and cost efficiency of the system. In the quest to improve energy management systems (EMS) and enhance power quality, a bi-level optimization approach named Particle swarm optimization-Modified water wave optimization (PSO-MWWO) has been proposed. This method integrates adaptive population size and an adaptive wavelength coefficient to boost its overall effectiveness. It is attractive with specialists in energy management systems (EMS), control systems, and hydrogen technologies can significantly augment the efficiency of coordination endeavours. PSO-MWWO can incorporate environmental considerations, such as minimizing emissions or exploiting the use of renewable energy resources (RESs) in hydrogen production and consumption. This paper thoroughly examines its implementation, operation, and unique features, with a particular emphasis on the power quality of a hydrogen based microgrid. The achieved results and numerical analysis affirm the superiority of the proposed technique compared to other traditional methods like mixed integer linear programming (MILP), HOMER, Variable mesh optimization (VMO), and Cataclysmic genetic algorithm in optimizing component sizing, renewable production, hydrogen production, reliability, cost effective, and overall efficacy. This substantiates its practical utility in real-time applications. The efficacy of this method is empirically demonstrated through the implementation in MATLAB software.